PELINDUNGAN HUKUM PEKERJA TERHADAP KETIDAKSESUAIAN PELAPORAN UPAH YANG DIDAFTARKAN KE BPJS OLEH PERUSAHAAN (STUDI KASUS PT MLG) - RIANA, ANA (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2025)
Abstract This research examines legal protection for workers at PT MLG through the lens of the legal protection theory proposed by Muchsan. The study aims to analyze the implementation of legal protection in labor practices, particularly concerning wage reporting to BPJS and worker registration. Data collected through interviews and observations reveal discrepancies in wage reporting and the lack of registration for all workers in BPJS, resulting in vulnerabilities to violations of workers' rights. This study employs an empirical normative approach, utilizing both field research and library research methods. In the context of legal protection, Muchsan's theory emphasizes the importance of two approaches: preventive and repressive legal protection. The findings of this study recommend the need for evaluation of labor oversight processes and increased awareness among all stakeholders, including employers, workers, and the government, to ensure the protection of workers' rights in accordance with applicable legal provisions. By implementing these measures, it is expected that legal protection at PT MLG can be enhanced, reducing violations and supporting the welfare of workers, thereby fostering a healthier and more sustainable industrial climate. Keywords: Legal Protection, BPJS, Wages